Why subclinical involvement is prescribed the same high dose as gross tumor volume: A study on high‐dose clinical target volume in intensity‐modulated radiotherapy plan of nasopharyngeal carcinoma. Issue 5 (1st March 2023) - Qiu, Zichen; Lin, Feifei; Wu, Zheng; Wu, Taihua; Wang, Mingli; Hu, Jiang; Xie, Dehuan; Lyu, Shaowen; Ma, Jun; Tao, Yalan; Su, Yong
Abstract: Background: Most nasopharyngeal carcinoma (NPC) protocols define primary gross tumor volume (GTVnx) plus a range from 2 to 5 mm as the high‐dose clinical target volume (hd‐CTV). However, in China, hd‐CTV is defined as GTVnx plus 0 mm. Methods: A total of 40 patients with newly diagnosed nonmetastatic NPC (T1–T4 ten cases each) treated with IMRT were consecutively enrolled. Real and virtual treatment plans were designed according to the definitions of hd‐CTV recommended by China and Radiation Therapy Oncology Group (RTOG), respectively. Results: The hd‐CTV in China was significantly smaller than that of RTOG. Exposure doses to 5 mm subclinical involvement and OARs as well as NTCP in the China treatment plan were significantly lower than those of RTOG. Conclusion: It could be recommended to divide the hd‐CTV into GTV and subclinical target volume and to prescribe different doses for the GTV and subclinical involvement in the IMRT plan of NPC.